Marine and coastal ecosystem valuation, institutions, and policy in Southeast Asia - Olewiler, Nancy D.; Francisco, Herminia Arocena-; Ferrer, Alice Joan G.; Ohio Library and Information Network
This book is a compendium of case studies illustrating how economic tools and techniques can be used to address a wide range of problems in the management and conservation of marine and coastal ecosystems in a developing country context. The studies, which were conducted with support from the Economy and Environment Program for Southeast Asia (EEPSEA), cover topics such as mobilizing conservation finance from beneficiaries of marine and coastal ecosystem services; quantifying ecosystem damage and its impact on dependents of ecosystem resources and services; determining the best package of policy reforms that put a price on pollution and regulate economic activities generating pollution with the goal of restoring coastal and marine resources; and analyzing community-based institutions that support sustainable management of fisheries and coastal resources. Studies in the book also provide general guidelines for conducting economic appraisals.
Chapter 4: Conservation Versus Development: Valuation of Coral Reefs Questions Port Expansion Plan in Vietnam4.1 Introduction; 4.2 Objectives of the Study; 4.3 Methodology; 4.3.1 Valuation Methodology: The Zonal Travel Cost Model (ZTCM); 4.3.2 Zonal Travel Cost Model (ZTCM); 4.3.3 Data Collection Techniques; 4.3.3.1 Collection of Secondary Data; 4.3.3.2 Collection of Primary Data; 4.3.3.3 Sampling; 4.3.4 Characteristics of the Study Area: Resources and Threats; 4.4 The Tourism Industry in Nha Thrang; 4.4.1 Socioeconomic Characteristics of Tourists.
Includes bibliographical references and index.
Ava Avila
Keywords: Marine ecosystem management -- Southeast Asia; Coastal zone management -- Southeast Asia; Electronic books; Electronic books